Integrating lignin depolymerization with microbial funneling processes using agronomically relevant feedstocks. Issue 7 (10th March 2022) - Perez, Jose M.; Sener, Canan; Misra, Shamik; Umana, German E.; Coplien, Jason; Haak, Dennis; Li, Yanding; Maravelias, Christos T.; Karlen, Steven D.; Ralph, John; Donohue, Timothy J.; Noguera, Daniel R.
Abstract : This work shows the integration of reductive lignin depolymerization and microbial funneling with Novosphingobium aromaticivorans to produce 2-pyrone-4, 6-dicarboxylic acid (PDC) in a lignocellulosic biorefinery. Abstract : The economic feasibility of the lignocellulosic biomass refinery requires the valorization of lignin in addition to its polysaccharide fraction. One promising approach is the combination of chemical methods for lignin fractionation and depolymerization with microbial funneling of the resulting phenolic monomers into valuable chemicals. In this work, we explored the integration of γ-valerolactone (GVL) for biomass pretreatment, catalytic hydrogenolysis for lignin depolymerization, and microbial funneling to 2-pyrone-4, 6-dicarboxylic acid (PDC) by the engineered bacterium Novosphingobium aromaticivorans strain PDC. We first investigated the microbial PDC production feasibility from common phenolic compounds previously identified in lignin hydrogenolysis products. Next, we studied the PDC production potential from maple, poplar, sorghum, and switchgrass using the proposed integrated pipeline and, finally, we performed a technoeconomic analysis (TEA) of the system to identify parameters that affect its economic feasibility. We found that N. aromaticivorans strain PDC is able to produce PDC from phenolic compounds with propanol, methyl, or methyl ester sidechains. Using Pd/C as a catalyst for hydrogenolysis to favor the production of these phenolics from lignin extracted with the GVL process, we obtained microbial PDC production yields of 88, 139, 103, and 79 g PDC per kg lignin from maple, poplar, sorghum, and switchgrass, respectively. Using these yields, we estimated a baseline minimum selling price of 12.10 per kg of purified PDC, and identified options to further improve the integrated pipeline.